STING-dependent cytosolic DNA sensing mediates innate immune recognition of immunogenic tumors - Woo, Seng-Ryong; Fuertes, Mercedes B; Corrales, Leticia; Spranger, Stefani; Furdyna, Michael J; Leung, Michael Y K; Duggan, Ryan; Wang, Ying; Barber, Glen N; Fitzgerald, Katherine A; Alegre, Maria-Luisa; Gajewski, Thomas F (Immunity (Cambridge, Mass.), 2014)
Spontaneous T cell responses against tumors occur frequently and have prognostic value in patients. The mechanism of innate immune sensing of immunogenic tumors leading to adaptive T cell responses remains undefined, although type I interferons (IFNs) are implicated in this process. We found that spontaneous CD8(+) T cell priming against tumors was defective in mice lacking stimulator of interferon genes complex (STING), but not other innate signaling pathways, suggesting involvement of a cytosolic DNA sensing pathway. In vitro, IFN-? production and dendritic cell activation were triggered by tumor-cell-derived DNA, via cyclic-GMP-AMP synthase (cGAS), STING, and interferon regulatory factor 3 (IRF3). In the tumor microenvironment in vivo, tumor cell DNA was detected within host antigen-presenting cells, which correlated with STING pathway activation and IFN-? production. Our results demonstrate that a major mechanism for innate immune sensing of cancer occurs via the host STING pathway, with major implications for cancer immunotherapy.